Hash-based message authentication code with secure hash algorithm-256 for efficient data sharing in blockchain - Lingaraju, Naveenkumar; Sunkadakatte, Manjula Haladappa (Institute of Advanced Engineering and Science, 2025)
Recently, cloud servers have increasingly been utilized for storing a large amount of data, which is stored in the form of ciphertext. In a decentralised system, the communication overhead on the network is recognized as the main problem due to the numerous transaction data recorded across the data Sharding and nodes with authorized users. Hash-Based Message Authentication Code with Secure Hash Algorithm-256-bit (HMAC-SHA-256 bit) is proposed for secure and effective data sharing in blockchain to overcome this issue. The secure algorithm HMAC serves for authenticating both the data origin and integrity. That uses a cryptographic hash procedure in combination with a confidential key to validate both the verification and tamper-proof content of a message. HMAC consists of a particular content and an authentication key with a hashing code value. In the Blockchain framework, the HMAC algorithm is utilized with the SHA-256bits to generate and validate the signatures of many transactions. SHA-256 is a hash algorithm that creates a 256-bit cryptographic checksum. The blockchain uses HMAC along with SHA-256bits, which is a safe and clearly expressed algorithm to allocate or convey the data securely. The Authentication of HMAC-SHA-256bits achieves the optimal retrieval times of 0.4s, 1.0s, 1.5s, 1.9s, 2.2s, and 2.8s for file sizes of 50KB, 100KB, 150KB, 200KB, 250KB, and 300KB, correspondingly, when compared to interplanetary file system (IPFS).